Submarine power cable between Europe and North America: A techno-economic analysis. (10th June 2018) - Purvins, Arturs; Sereno, Luigi; Ardelean, Mircea; Covrig, Catalin-Felix; Efthimiadis, Tilemahos; Minnebo, Philip
Abstract: Increasing the deployment of power generators using variable renewable power sources, such as wind and solar, brings power balancing challenges in electricity systems. One mean to achieve power balancing and to share balancing resources, is to interconnect electricity systems to geographically aggregate remotely located variable power sources. This article addresses this potential and provides insights for electricity trading through a submarine power cable between Europe and the eastern part of North America. While such ambitious power interconnection concepts appear in recent literature, this article is the first to present a techno-economic analyses. This article concludes that, a 4000 MW cable between Europe and North America could bring an annual socio-economic benefit of 177 M€ in 2030. In addition to the differences in generation costs, mutual benefits from electricity trading between Europe and North America derive from different daily peak demand times, low correlation in generation from renewable energy sources, and in seasonal demand variations. The results of the cost-benefit analysis indicate that the benefit for society is sufficient to cover the investment costs. Thus, the proposed interconnector is welfare improving. Graphical abstract: Image Highlights: Developed a 2030 power dispatch model of Europe and North America (NA). Identified socio-economic benefits of European-NA electricity trading through a HVDC cable. A 4000 MW cable increases social welfare by 177 M€ on an annual basis. This benefit for society is sufficient to cover the investment costs.